Effects of vitamin D supplementation and floor space on pig performance - Flohr, Joshua Richard (Kansas State University, 2015)
Three experiments using 2,385 pre-weaned pigs, growing pigs, and sows were performed in addition to a meta-analysis and industry survey. Experiment 1 tested the effects of sow vitamin D supplementation from vitamin D₃ (low, medium, or high) or 25OHD₃ (same IU equivalency as the medium level of vitamin D₃) on maternal performance, neonatal pig bone and muscle characteristics, subsequent pre-weaned pig performance and serum 25OHD₃ with only differences in serum 25OHD₃ being impacted. In the second experiment a subsample of pigs weaned from the maternal portion of the study were used in a split-plot design and fed 2 different forms of vitamin D in the nursery and growth performance was evaluated until the pigs reached market weight. Overall, the nursery vitamin D treatments did not impact growth; however, pigs from sows fed the medium level of vitamin D₃ performed better after weaning compared to pigs from sows fed the low or the high level of vitamin D₃, and serum 25OHD₃ was altered based on maternal and nursery vitamin D supplementation. In the third experiment, finishing pigs were initially provided 2 different floor space allowances (0.64 or 0.91 m²) and pigs initially provided 0.64 m² were subject to 1 of 3 marketing strategies which removed the heaviest pigs from the pen in order to provide additional floor space to the pigs remaining in the pen. Overall, pigs initially provided more floor space had improved ADG and ADFI, but increasing the number of marketing events increased ADG of the pigs remaining in the pen following market events. The meta-analysis suggested that a multi-term empirical model using random effects to account for known error and weighted observations to account for heterogeneous experimental designs and replication provided models that best fit the database. Also, the meta-analysis concluded that floor space allowance does influence ADG, ADFI, and G:F and BW of the pig can alter the floor space response. Finally, the vitamin and trace mineral survey suggested that a wide range of supplementation practices are used in the swine industry but most production systems supplement micronutrients above the basal requirement estimates of the animals.
Keywords: Vitamin D; Floor space; Prediction equations; Sow; Finishing pig; Nursery pig; Agriculture, General (0473); Animal Sciences (0475); Statistics (0463)